Concise enantioselective synthesis of (+)-sertraline and (-)-CP-52002 using proline catalysis - Kalshetti, Rupali G.; Venkataramasubramanian, V.; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (+)-sertraline and its C-4 epimer (-)-CP-52002 with an overall yield of 30%, respectively, as its hydrochloride has been described. The key steps are the proline catalyzed Mannich reaction of acetaldehyde and acid catalyzed intramolecular Friedel-Crafts' alkylation reaction of olefin proceeding with high optical purities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Indatraline; Mannich reaction; Proline catalysis; Sertraline; Tametraline

I-2-mediated regioselective C-3 azidation of indoles - Prasad, Pragati K.; Kalshetti, Rupali G.; Reddi, Rambabu N.; Kamble, Sanjay P.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2016)
An unprecedented synthesis of novel 3-azido indoles has been developed using I-2 and NaN3 in high yields and excellent regio-selectivity. The reaction proceeds under metal-free conditions at room temperature. Essentially, an umpolung in reactivity at the C-3 position of indole has been achieved by the activation of indoles with I-2.

Concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol using Co(III)(salen)-catalyzed hydrolytic kinetic resolution of a two-stereocentered anti-azido epoxide - Reddi, Rambabu N.; Prasad, Pragati K.; Kalshetti, Rupali G.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2017)
A concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol, (+)-DAB-1, has been described in good overall yield (18.1%) and with high enantiomeric purity (up to 98% ee) starting from a simple raw material, cis-2-butene-1,4-diol. The Co-catalyzed hydrolytic kinetic resolution of a two-stereocentered racemic azido epoxide followed by asymmetric dihydroxylation of the alkene and 'one pot' reductive cyclisation of the azido diol are key reactions in the synthetic sequence. (C) 2016 Elsevier Ltd. All rights reserved.

Iridium(III)-catalyzed alkynylation of 2-(Hetero)arylquinazolin-4-one scaffolds via C-H bond activation - Rohokale, Rajendra S.; Kalshetti, Rupali G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
The directed C-H alkynylation of 2-(hetero)arylquinazolin-4-ones has been explored with the ethynylbenziodoxolone reagent TIPS-EBX employing an Ir(III) catalyst. Complementary conditions for either monoalkynylation or dialkynylation have been developed. Also demonstrated is the broad scope of this reaction and the compatibility of various functional groups such as -F, -Cl, -Br, -CF3, -OMe, -NO2, and alkyl, etc.

Oxidative rearrangement of stilbenes to 2,2-diaryl-2-hydroxyacetaldehydes - Kalshetti, Rupali G.; Ramana, V. Chepuri (ACS Omega, 2020)
A one-pot oxone-mediated/iodine-catalyzed oxidative rearrangement of stilbenes leading to 2,2-diary1-2-hydroxyacetaldehydes is described. Control experiments revealed that a 2,2-diarylacetaldehyde was initially formed that undergoes subsequent alpha-hydroxylation. The resulting alpha-hydroxyaldehydes have been subjected to a one-pot Still Gennari olefination followed by cyclization, leading to S,S-diaryl-y-butenolides.

P2O5-mediated Friedel-Crafts acylation of activated arenes with carboxylic acid as acylating agent - Kalshetti, Rupali G.; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
P2O5 has been found to be a highly efficient and environmental friendly catalyst for the liquid-phase acylation of activated aromatic substrates giving aromatic ketones (45-93%) in a regioselective manner. Both aromatic and aliphatic carboxylic acids can be employed as acylating source. The process is particularly demonstrated at 100 g scale in the case of anisole and acetic acid to produce 4-methoxyacetophenone.
Keywords: 4-methoxyacetophenone; Carboxylic acid; Friedel-Crafts acylations; phosphorus pentoxide

Ru-catalyzed asymmetric transfer hydrogenation of alpha-acyl butyrolactone via dynamic kinetic resolution: asymmetric synthesis of bis-THF alcohol intermediate of darunavir - More, V. Ganesh; Malekar, V. Pushpa; Kalshetti, Rupali G.; Shinde, Mahesh H.; Ramana, V. Chepuri (Tetrahedron Letters, 2021)
The Ru-catalyzed enantio- and diastereoselective dynamic kinetic resolution of alpha-(benzyloxy/benzoyloxy)acyl-gamma-butyrolactones has been examined via transfer hydrogenation. Employing the in situ prepared (R,R)-Ru-FsDPEN catalyst, the transfer hydrogenation of using formic acid/triethylamine at rt gave the corresponding (S)-3-((S)-2-(benzyloxy/benzoyloxy)-1-hydroxyethyl)dihydrofuran-2(3H)-on e with good to excellent diastereo- and enantioselectivity. One of the resulting hydrogenation product prepared on gram scales was utilized for the synthesis of (3R,3aS,6aR)-hexahydrofuro[2,3-b]furan-3-ol (1), a key synthetic intermediate of various HIV protease inhibitors such as darunavir with excellent enantio-(95% ee) and diastereoselectivities (dr 95:5). (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF-OH intermediate; Darunavir; Dynamic kinetic resolution; Ru-catalysis; transfer hydrogenation

Postmodification of voxelotor (GBT 440) via [Rh]-catalyzed cross dehydrogenative coupling with olefins br - Kalshetti, Rupali G.; Rajput, Raveena; Motiwala, Zenia; Reddy, D. Srinivasa; Kulkarni, Kiran A.; V. Ramana, Chepuri (Bioorganic & Medicinal Chemistry Letters, 2022)
The directed Rh(III)-catalyzed cross dehydrogenative coupling of the pyrazole unit of the GBT-440 scaffold has been explored with simple as well as conjugated olefins to synthesize post-functionalized GBT-440 analogues. The screening of these synthesized compounds for improving the oxygen binding efficiency of the hemoglobin isolated from the sickled red blood cells revealed that some of these compounds are as good as GBT-440.
Keywords: CDC Coupling; GBT-440 (Voxelotor); Rh(III) catalysis; sickle cell anemia

Rh-catalyzed C-H functionalization of the (Pyrazol-5-yl)pyridine core of GBT-440 - Kalshetti, Rupali G.; Halnor, Swapnil V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2023)
The Rh-catalyzed cross dehydrogenative coupling (CDC)/alkylation of the pyrazolylpyridine unit of GBT-440 proceeded smoothly under ambient conditions and selectively on the pyrazole unit while directed by the pyridine. The scope of these reactions was established by employing simple as well as conjugated olefins for CDC and various diazo esters and the TIPS-EBX reagent for alkylation. At the outset, a focused small molecule library around the bis-heterocyclic core of GBT440 was developed via C-H functionalization.
Keywords: C-H activation; cross dehydrogenative coupling; diazo ester; GBT-440; Rh catalysis; TIPS-EBX